ANALISIS KINERJA KARYAWAN DALAM MENINGKATKAN KESEJAHTERAAN ANGGOTA PADA PT.INDAH LOGISTIK CARGO - Fandra Dikhi Januardani; Joko Susilo; Rosintan Sipayung; Jesika Melina Simamora (Politeknik Bisnis Indonesia, 2024)
High performance can be obtained by improving quality labor. The quality of the workforce can be seen from increased engagement work, increased job satisfaction, decreased stress, decreased number work accidents and the number of employee absences. The company prioritizes the welfare of employees so that they remain good servants to customers. The more employees who have high performance, the company's overall productivity will increase so that the company will be able to survive in global competition. Employees are also required to be able to complete the tasks within their responsibilities effectively and efficiently. Employee performance can also be measured through customer satisfaction and reducing the number of customer complaints and achieving optimal targets. This research aims to find out how much influence member welfare has on employee performance at PT.INDAH LOGISTIK CARGO, Pematangsiantar City, both partially and simultaneously. The research method used was quantitative with a sample size of 41 employees. The data collection techniques used were interviews, observation, questionnaires. The data analysis methods used are multiple linear regression, multiple correlation, coefficient of determination, and hypothesis testing. Based on the research results, it shows that simultaneously member welfare and work discipline have a positive and significant effect on employee performance at PT.INDAH LOGISTIK CARGO, Pematangsiantar City. Judging from the results of the analysis of the coefficient of determination, it is stated that the welfare of members greatly influences employee performance. This can be seen from the partial or individual influence, and the smaller influence on employee performance